Experimental Analysis on Cooling Channels Parameters in Hot Stamping Tools (SKD61) - M. Farid, M. Sharif; M. A. Hanafiah, Saharudin; M. Shaifil Hakimin, M. Sakri; Nur Asyran Wani, Baharom (AENSI Publisher, 2014)
Hot stamping technology has attracted enormous attention among researchers, particularly on reducing the weight of vehicles whilst improving vehicle crash compatibility and also lowering down the greenhouse gas emissions. Through this technology it is feasible to combine forming and quenching in a single process, so that complex geometric shapes and high strength automotive components can be manufactured. The key factor to optimize the cycle time of this process actually lies in the cooling channels system that acts to cool down the tool efficiently. For this reason, an experimental analysis on cooling channels parameters, which include cooling channel configurations, water flow rates and stamping time in die, have been carried out. The materials used for the specimen tests were the quenchable high strength boron manganese 22MnB5 sheet metal, while hot work die steel SKD61 that comprises of flat punch and die was used as the tool set. To investigate the parameters, the specimens were heated to the austenization temperature of 950°C and immediately quenched in the water-cooled die. The findings revealed that the highest tensile strength could be achieved at the parameter of the lengthiest stamping time in die, the fastest water flow rate and the nearest cooling channel to the tool-part interface. Hence, these cooling channels parameters have to be taken into account in designing the tool for hot stamping process.